Applicability of Concentrations Obtained by Working Environment Measurement to Assessment of Personal Exposure Concentrations of Chemicals. Issue 2 (3rd October 2014) - Yamamoto, Shinobu; Natsumeda, Shuichiro; Hara, Kunio; Yoshida, Satoru; Sakurai, Haruhiko; Ichiba, Masayoshi
Abstract : Applicability of Concentrations Obtained by Working Environment Measurement to Assessment of Personal Exposure Concentrations of Chemicals: Shinobu YAMAMOTO, et al . Kyushu Regional Safety and Health Service Center, Japan Industrial Safety and Health Association— Objective: This study determined the applicability of Japanese working environment measurements to assessment of personal exposure concentrations of chemicals by comparing both levels of concentrations. Methods: The chemicals measured in this study comprised eight kinds of vaporous chemicals as well as two kinds of chemicals in dust. Personal exposure measurements, Japanese working environment measurements and spot sampling measurements were undertaken in 70 companies. Results: Personal exposure concentrations and the arithmetic mean value (EA2 ) of the working environment measurement concentrations obtained according to the Japanese working environment control system had statistically positive correlations (r=0.732−0.893, p <0.01) after logarithmic transformation. The 5th to 95th percentile values of personal exposure concentrations divided by EA2 ranged from 0.17 to 7.69 for vaporous chemicals and from 0.27 to 18.06 for dust. There was a relatively large difference between the personal exposure concentrations and the EA2 obtained in weighing, forming and bonding use‐processes. In such cases, the B‐value measured in ten minutes in the Japanese working environment control system, which is almost the same as the spot measurement concentration in this study, is supposed to be substituted for the EA2 value. Conclusions: Ten times the EA2 of the working environment measurement concentrations, or ten times the B‐value, obtained according to the Japanese working environment control system can be used to conservatively estimate the personal exposure concentrations in EU workplaces as well as in occupational exposure scenarios of the Regulation on Registration, Evaluation, Authorisation and Restriction of Chemicals.